2018
DOI: 10.1177/1055665618770192
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Orofacial Clefting in New York City From 1983 to 2010

Abstract: The period prevalence remained relatively stable during the time periods before and after the implementation of folate supplementation for OFCs in NYC. Prevalence of OFC subtypes was lower for most time periods during this study among African Americans compared to whites. Several factors may explain the choice of birthplace outside of the mother's borough of residence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…It could be explained by underregistration, internal migration phenomenon, or due to low association of CL/P with ethnical groups. 31 Bogotá and its surroundings are in the center of the country and show a particular pattern compared to other regions of the country. Bogotá has the highest concentration of the CL/P population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It could be explained by underregistration, internal migration phenomenon, or due to low association of CL/P with ethnical groups. 31 Bogotá and its surroundings are in the center of the country and show a particular pattern compared to other regions of the country. Bogotá has the highest concentration of the CL/P population.…”
Section: Discussionmentioning
confidence: 99%
“…It could be explained by under-registration, internal migration phenomenon, or due to low association of CL/P with ethnical groups. 31…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the two clefts are embryologically the same. 1 , 2 , 3 , 4 , 5 Clinically, several cases of cleft lip without cleft alveolus have been reported, but no case of complete cleft alveolus without cleft lip, even microform cleft lip, has been reported. Nagase et al showed 102 patterns of cleft lip and/or cleft palate in Japanese patients using 17 classification codes.…”
Section: Discussionmentioning
confidence: 99%
“…Cleft lip and/or cleft palate are frequently occurring external anomalies and have shown higher incidence rates in the Japanese population than that in other ethnic groups. 1 , 2 , 3 Embryologically, incomplete fusion of the facial prominences; specifically, incomplete fusion of the frontonasal and maxillary prominences could lead to cleft lip and/or cleft alveolus. 4 , 5 A complete cleft lip is caused by a complete failure of fusion between the frontonasal and maxillary prominences, whereas incomplete fusion in some areas can result in an incomplete cleft lip.…”
Section: Introductionmentioning
confidence: 99%
“…North America range from 0.54 to 1.62 per 1000 and probably represent diverse racial groups. 2,22 A 10-year study on 3804 cleft patients in California, United States, found the highest incidence in Native Americans and lowest in African Americans. Whites, Japanese, and Chinese were of intermediate incidence with no significant differences between them.…”
mentioning
confidence: 99%